Dynamic analysis of hybrid basalt and carbon fiber reinforced Bismaleimide composites suited for high temperature structural applications. (10th December 2021) - Iyer, N Prasanaa; Arunkumar, N
Abstract: The main aim of this work is to study thedamage tolerance of hybrid basalt and carbon fiber-reinforced composite subjected to low velocity impact (LVI) at different velocities, 2.89 m s −1 and 4.42 m s −1, simulated using a CEAST drop hammer testing machine and Dynamic Mechanical Analysis(DMA) were conducted to characterize the sample. In this article, the detailed failure mechanism of seven composite laminates (Basalt fiber/Bismaleimide(BMI)-diallyl Bisphenol A(DABA), Carbon fiber/BMI-DABA, Carbon and basalt fiber(hybrid fibers)/BMI-DABA) were studied under loading of LVI. Through the experiment, it was also substantiated that the hybrid fiber-reinforced composites possessed better damage tolerance and thermo mechanical properties than the homogenous fiber-reinforced composites. The hybrid fiber composites that were produced vary in the number of carbon fiber to basalt fiber ratio and stacking sequence. The impacted surface was analyzed at macro level by using Image J software. The impact force, the energy absorbed, and the deformation of the laminates under impact load were scrutinized extensively, and it was inferred that the basalt fiber intercalated with carbon fiber with BMI/DABA possessed the highest damage resistance than the other composite laminates under study. The highest peak force 5702 N and 9241 N with the highest elastic energy 4.8 J, 11.7 J and with lower deformation (3.85 mm, 6.09 mm) and deformation area (22.79 mm 2, 28.09 mm 2 ) was observed in the intercalated hybrid laminate.